Aplicación de un recubrimiento comestible a base de mucílago de nopal (opuntia ficus-indica) y aceite esencial de matico (buddleja globosa) para la conservación de la mora de castilla (rubus glaucus). - Rodríguez Andachi, Evelin Abigail (2023)
The purpose of this research project was to evaluate the application of an edible coating based on cactus mucilage (Opuntia ficus-indica) and matico (Buddleja globosa) essential oil for the conservation of blackberry (Rubus glaucus). To carry out the study, an A x B factorial design was established to determine the optimal concentrations of nopal mucilage and matico essential oil; 86% of cactus mucilage and 10% of matico oil were fixed, along with 0.10% of pectin. Additionally, 10% glycerol, 1% carboxymethylcellulose, 0.10% tween 80 were included as a plasticizer, and the formulation was completed with 3.8% distilled water. When evaluating the physicochemical parameters after 15 days, treatment 1 stood out the most, yielding the following results: weight loss 5.36%, a concentration of soluble solids of 13.7% degrees Brix, a pH of 3, 02, a titratable acidity with a value of 2.12%, with a maturity index of 6, in addition to a visual color scored at 6, finally this treatment presented molds after 15 days. Therefore, the Edible Coating is a good alternative and opportunity for farmers as well as merchants who work with this highly perishable fruit; The adoption of this technique has the potential to provide notable advantages in terms of preserving and improving the quality of the final product.